Extinction risk and conservation gaps for Aloe (Asphodelaceae) in the Horn of Africa - Steven P. Bachman; Paul Wilkin; Tom Reader; Richard Field; Odile Weber; Inger Nordal; Sebsebe Demissew (Biodiversity and Conservation, 2020)
Identification of conservation priorities is essential for conservation planning, especially as the biodiversity crisis develops. We aimed to support conservation prioritisation by addressing knowledge gaps for the genus Aloe in the Horn of Africa. Specifically, we developed a dataset of herbarium voucher specimens and occurrence data to estimate geographic distribution of 88 species of Aloe and used this to estimate extinction risk and establish the major threats to Aloe in this region. The resulting assessments, each published on the IUCN Red List, show that 39% of the species are threatened with extinction, and the principal threats are the expansion and intensification of crop farming and livestock farming, gathering of plants, and unintentional effects of logging and wood harvesting. We review ex situ conservation in botanic gardens and seed banks, revealing gaps in coverage and urgent priorities for collection, with 25 threatened Aloe species currently unrepresented in seed banks. Protected areas in the region offer limited coverage of Aloe distributions and the most recently designated protected areas are increasingly in regions that do not overlap with Aloe distributions. However, we show with a simple optimisation approach that even a modest increase in protected area of 824 square kilometres would allow representation of all Aloe species, although further data are needed to test the area required to ensure long-term persistence (resilience) of Aloe species.